Peran Strategis Pemerintah Daerah dalam Meningkatkan Kualitas Pelayanan Publik - Norwanda Norwanda; Wulan Sri Wahyuni; Nadia Irani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the role of local governments in improving the quality of public services as part of an initiative to achieve responsive governance that prioritizes the public interest. This study departs from the limitations of previous research, which tends to focus on the technical aspects of service quality, while the strategic role of local governments as the primary actors in improving the quality of public services remains underexplored. The purpose of this study is to analyze the role of local governments in improving the quality of public services and identify factors influencing the optimization of this role. The method used in this study is a qualitative approach through a literature review analyzing various secondary sources such as scientific books, national and international journals, regulations, and reports from relevant official institutions. The study findings indicate that local governments play a significant role in improving the quality of public services through three main dimensions: a community-focused service orientation, technology-based service innovation, and strengthening inclusive and collaborative service management. The integration of these three dimensions supports more efficient, transparent, and responsive public services to community needs. This research provides a conceptual contribution to the field of public administration, emphasizing the importance of strengthening the role of local governments as a key factor in sustainably improving the quality of public services.